Urinary transforming growth Factor-Beta 1 (uTGF-β1) and prevalent CKD risk in HIVpositive patients in West Africa (2019)
Introduction: This study investigated the association of urinary transforming growth factor-b1 (uTGF-b1) with prevalent chronic kidney disease (CKD) in the HIV-infected population. Methods: HIV-positive patients without CKD (HIVþCKD, n ¼ 194) and 114 with CKD (HIV CKD) who did not have hypertension, diabetes mellitus, or hepatitis B or C, had their urinary protein-creatinine ratio (uPCR), serum transforming growth factor (TGF)–b1, and uTGF-b1 measured. uTGF-b1-creatinine ratios (uTGF-b1Cr) were calculated. Spearman correlation was used to determine the association between uTGF-b1Cr and various attributes, and the Cuzick trend test was used to assess the presence of a linear trend in median uTGF-b1Cr levels across the stages of CKD. Multivariable robust linear regression models were used to assess independent association with variability in uTGF-b1Cr and estimated glomerular filtration rate (eGFR) levels. Results: The age of the participants was 38.3 0.3 years with 73.4% women. The median uTGF-b1Cr was higher among HIV CKD (4.85 ng/mmol [25th–75th percentile 1.96–12.35] vs. 2.95 [1.02–5.84]; P ¼ 0.001]). There was significant correlation between uTGF-b1Cr and age (P ¼ 0.02), eGFR (P ¼ 0.001), and uPCR (P < 0.001) in the HIV CKD group. Among the HIV CKD patients, there was gradual reduction in the median level of uTGF-b1Cr with CKD severity (P ¼ 0.04). HIV CKD patients had significantly higher levels of uTGF-b1Cr after controlling for potential confounders. Using eGFR as dependent variable, proteinuria explained the changes associated with uTGF-b1Cr levels. Conclusion: HIV CKD patients express higher levels of uTGF-b1 especially in the early stages of CKD apparently related to proteinuria levels.